Predictive and prognostic value of serum periostin in advanced non–small cell lung cancer patients receiving chemotherapy. Issue 5 (April 2017) - Zhang, Yan; Yuan, Dongmei; Yao, Yanwen; Sun, Wenkui; Shi, Yi; Su, Xin
Periostin is an extracellular matrix protein involved in tumorigenesis and metastasis. However, the role of serum periostin as a surrogate marker for treatment efficacy is still unknown. In 122 advanced non–small cell lung cancer cases, 37 patients with benign lung disease and 40 healthy controls, serum periostin was measured by enzyme-linked immunosorbent assays. The associations of serum periostin levels with the clinic-pathological parameters, chemotherapy response, and clinical outcomes of non–small cell lung cancer patients were analyzed. Serum periostin levels were significantly higher in non–small cell lung cancer patients, and it was related significantly to bone metastasis ( p  = 0.021). Serum periostin of 65 non–small cell lung cancer patients were detected before and after two cycles of chemotherapy. The patients with and without periostin response had significant difference in objective response to chemotherapy ( p  = 0.001). For the 122 non–small cell lung cancer patients, the median progression-free survival was 5 months. In a multivariate analysis, performance status (hazard ratio, 1.71; 95% confidence interval, 1.10–2.67), baseline periostin (hazard ratio, 1.01; 95% confidence interval, 1.00–1.01), and periostin response (hazard ratio, 0.50; 95% confidence interval, 0.29–0.86) were significantly correlated with prognosis. In conclusion, serum periostin was elevated in advanced non–small cell lung cancer patients. Baseline periostin and periostin responses appeared to be reliable surrogate markers to predict chemotherapy response and survival in patients with advanced non–small cell lung cancer.